2019
DOI: 10.1002/hep.30333
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Nonalcoholic Steatohepatitis: Toward Optimization of Their Relevance to Human Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic steatohepatitis (NASH) arises from a variable interplay between environmental factors and geneticdeterminants that cannot be completely replicated in animals. Notwithstanding, preclinical models are needed to understand NASH pathophysiology and test mechanism-based therapies. Among several mouse models of NASH, some exhibit the key pathophysiologic as well as histopathologic criteria for human NASH, whereas others may be useful to address specific questions. Models based on overnutrition with adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
223
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(258 citation statements)
references
References 52 publications
10
223
0
4
Order By: Relevance
“…In our study, we have established two entirely different murine models of steatohepatitis, both of which have been extensively used in NASH research but emphasizing different characteristics and mechanisms regarding steatohepatitis (31 (31,32). RIP1 kinase-dead (Rip1 K45A/K45A ) mice exhibited significantly attenuated liver injury, inflammation as well as fibrosis in both models, suggesting that the involvement of RIP1 kinase in NASH pathogenesis is not limited to specific model, but might generally apply to models induced by different factors or conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we have established two entirely different murine models of steatohepatitis, both of which have been extensively used in NASH research but emphasizing different characteristics and mechanisms regarding steatohepatitis (31 (31,32). RIP1 kinase-dead (Rip1 K45A/K45A ) mice exhibited significantly attenuated liver injury, inflammation as well as fibrosis in both models, suggesting that the involvement of RIP1 kinase in NASH pathogenesis is not limited to specific model, but might generally apply to models induced by different factors or conditions.…”
Section: Discussionmentioning
confidence: 99%
“…more prominent fibrosis, such as the choline-deficient L-amino-defined diet could have been used. 2 Ex vivo, the authors confirmed ARRB1 expression in hepatocytes but not in Kupffer cells, suggesting that the increased macrophage infiltration found in Arrb1 knockout mice was secondary to hepatocyte damage. Moreover, overexpression of ARRB1 in human HepG2 cells and primary murine hepatocytes attenuated lipid accumulation after palmitate-supplementation, and decreased the expression of lipogenesis-associated genes, while downregulation of ARRB1 enhanced the expression of NFkB p65, promoting hepatocyte inflammatory pathways.…”
mentioning
confidence: 88%
“…1 A central molecular driver of progression is lipotoxicity, a process involving multiple lipid species and pathways that result in hepatocyte damage, liver inflammation and fibrogenesis. 2 b-arrestin1 (ARRB1), 1 of the 2 b-arrestin isoforms, was initially described as a central regulator of G-protein-coupledreceptor signaling via receptor desensitization and internalization. [3][4][5] ARRB1 and ARRB2 are ubiquitously expressed as intracellular proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-alcoholic fatty liver disease (NAFLD) is a highly active field of animal research [15,16] . NAFLD is a common condition characterised by increased liver fat (hepatic steatosis) that may progress to inflammation (non-alcoholic steatohepatitis (NASH)) and fibrosis [17] .…”
Section: Introductionmentioning
confidence: 99%